Production related problems in a small scale garment enterprise Carroza industries - Baltazar, Melody Perdigon
This study attempted to identify production related problems in a small garment enterprise; Carozza Industries, which specialize in children's and ladies' garments. Data were gathered through interviews with the owner-manager and production supervisor. In addition, the different stages in the production process were carefully observed and documented for a period of two and a half months. Results showed that among the more critical problems identified were incorrect pattern measurements, cutter's insufficient knowledge of fabric consumption and failure to meet production deadlines.